The production of subjection from Power and potency: A Deleuzian spill - Campillos Morón, Luis Ángel (Res Publica. Revista de Historia de las Ideas Políticas, 2024)
From the philosophy of Gilles Deleuze, in this article we will study the process of subjection, that is, how a certain Power reduces the potential of beings (human and others), turning them into subjects of its authoritarian order. Taking several concepts (plane of immanence, plane of consistency, Body-Without-Order), that traverse Deleuzian political ontology, we will analyze this process that generates impotence, we will analyze this generating process of impotence by pointing out three phases: closure, submission and vigilance. We will explain these three stages (strata) using some simple graphs that will facilitate understanding and promote their application to concrete current problems. Finally, in the conclusions, we will raise the animal concept (antagonist of the subject) as an expression of the CsO.
Keywords: Deleuze; Subject; Potency; Power; Body-without-Organs